Water management in deep peat soils in Malaysia - Zakaria, Salmah. (Cranfield University, 1992)
The study seeks to develop a field water management system for agriculture in peat soils in Malaysia, with an overall approach of integrating the engineering and agronomic aspects associated with crop production in deep peat areas. This includes the determination of soil physical parameters essential for field drainage design. The main experiments were carried out on a 10.9 hectare plot of land, initially drained 15 years earlier. The results were compared with data collected from a newly opened area and an area drained 40 years earlier. Cont/d.